'Seeing red': cultural studies in global comparison. Issue 4 (1st October 2016) - Tomaselli, Keyan G.
ABSTRACT: This paper critically examines 'the vague and baggy monster' that much cultural studies (CS) have become, how it has traveled and what utilitarian forms it assumes in totally different contexts and periods. The field, once known for its activist intellectualism, has been everywhere re-articulated into doing different kinds of work: translation, literary studies, marketing, audience, policy analysis and discourse analysis. One particular Chinese appropriation will be compared to British, Australian, South American, American and South African experiences. The discourse of Cultural China in understanding a globalized market economy following the end of the Cold War is examined. The implications for global CS are discussed in terms of ideological metaphors of the color 'red' (as in revolutions [cultural, political, guerilla] and in fashion).